Primary minute mucinous adenocarcinoma of vermiform appendix arising from appendiceal diverticulosis - Tadashi Terada, MD, PhD (Elsevier, 2015)
Primary mucinous adenocarcinoma (MA) of vermiform appendix is extremely rare; only three cases have been reported in the English literature. A 77-year-old man presented with abdominal pain, and was diagnosed with acute appendicitis. Appendectomy was performed. The resected appendix showed submucosal swelling measuring 0.7×0.6×0.6 cm in the tip of appendix. The appendix showed inflammation and numerous diverticuloses. Microscopically, the submucosal swelling was a mucin lake in which adenocarcinoma cells were floating. The adenocarcinoma cells were MA in 80% and signet-ring cell carcinoma in 20%. The carcinoma cells were located in the submucosa, muscular layer and subserosa, sparing the mucosa. No apparent lymphovascular permeation was seen. The surgical margins were negative for tumor cells. The non-tumorous appendix shows numerous diverticulosis, diverticulitis, and appendicitis. Immunohistochemically, the tumor cells were positive for CK CAM5.2, CK AE1/3, CK8, CK18, CK19, CK20, EMA, CEA, CA19-9, MUC1, MUC2, MUC5AC, MUC6, NCAM, p53 and Ki-67 (labeling index = 23%). The tumor cells were negative for CK34BE12, CD5, CK6, CK7, NSE, chromogranin, synaptophysin, CA125, KIT, and PDGFRA. No metastasis has been seen 2.5 years after the operation.